2020
DOI: 10.3389/fendo.2020.00421
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Techniques for Brown Adipose Tissue Detection

Abstract: Magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) methods can non-invasively assess brown adipose tissue (BAT) structure and function. Recently, MRI and MRS have been proposed as a means to differentiate BAT from white adipose tissue (WAT) and to extract morphological and functional information on BAT inaccessible by other means. Specifically, proton MR (1 H) techniques, such as proton density fat fraction mapping, diffusion imaging, and intermolecular multiple quantum coherence imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 189 publications
(318 reference statements)
0
35
0
2
Order By: Relevance
“…Adipose tissue is a highly specialized tissue and plays a key role in energy mobilization regulation ( Reilly and Saltiel, 2017 ; Zhai et al, 2020 ). Two types of adipose tissue have been found in mammals so far, called white adipose tissue (WAT) and brown adipose tissue (BAT) ( Cannon and Nedergaard, 2004 ; Wu et al, 2020 ). WAT is generally thought as an organ stores excess energy which maintains energy in the form of triglyceride in lipid droplets.…”
Section: Adipose Tissues and Obesitymentioning
confidence: 99%
“…Adipose tissue is a highly specialized tissue and plays a key role in energy mobilization regulation ( Reilly and Saltiel, 2017 ; Zhai et al, 2020 ). Two types of adipose tissue have been found in mammals so far, called white adipose tissue (WAT) and brown adipose tissue (BAT) ( Cannon and Nedergaard, 2004 ; Wu et al, 2020 ). WAT is generally thought as an organ stores excess energy which maintains energy in the form of triglyceride in lipid droplets.…”
Section: Adipose Tissues and Obesitymentioning
confidence: 99%
“…Recently, MRI begins to be used in BAT research studies as a nonradioactive imaging method. Since BAT has been shown to have different fractions of fatty acids and water content compared with those of WAT, BAT and WAT tissues can be distinguished by MRI [10].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are many kinds of methods for BAT research, such as proton density fat fraction (PDFF) and T2* mapping, however, these methods are complicated and need expensive device that limit their application. On the contrary, T2 mapping were widely used in the clinical routine, such as heart, cartilage evaluation and so on [8,9], so we think it may be a good candidate for BAT research [10].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased EFA and increased EFV were associated with higher cardiovascular risk [31]. Furthermore, the latest report suggested that it was EFA, but not EFV, is the independent predictor of obstructive CAD and high-risk plaque [32]. Regrettably, the two studied mentioned above only measured EF in CCS images [14,27], results after the introduction of the contrast agent were unknown.…”
Section: Discussionmentioning
confidence: 99%